An updated checklist of testate amoebae in China - Yangmin Qin; Yulin Zhu; Zixuan Lin; Daniel Puppe (Protist, 2026)

The importance of reactive silica for maintaining soil health - Jörg Schaller; Markus Kleber; Daniel Puppe; Mathias Stein; Michael Sommer; Matthias C. Rillig (Plant and Soil, 2025)
Background and aim Soil health is vital for the sustainability of ecosystem services such as food and fiber production, nutrient cycling and water supply. Soil health can be assessed through a combination of physical, biological and chemical metrics. There is emerging evidence that reactive silica is a strong factor controlling soil functions. Scope We explain how reactive silica, specifically dissolved silicic acid and amorphous silica, can be used as a new metric for assessing soil health, complementing traditional metrics or even substituting for them. Conclusion The pivotal role of reactive silica for soil health is particularly important under stress conditions that are typically associated with drought and soil degradation. The status of reactive silica indicates soil degradation earlier than the currently used metrics, because reactive silica depletion is followed by soil degradation. We recommend suitable methods and benchmarks for assessing reactive silica. Furthermore, we suggest further research to improve our understanding of the importance of reactive silica for soil health. We call upon the soil research community to include reactive silica as a metric for soil health assessment.

Testate amoebae (Protozoa) in lakes of the Qinghai-Tibet Plateau: Biodiversity, community structures, and protozoic biosilicification in relation to environmental properties and climate warming - Yangmin Qin; Anatoly Bobrov; Daniel Puppe; Hui Li; Baiying Man; Jing Gong; Jie Wang; Yongde Cui; Yansheng Gu; Ulrike Herzschuh; Shucheng Xie (Science of The Total Environment, 2024)

Infrared-based analysis of organic matter composition in liquid and solid runoff fractions collected during a single erosion event - Ruth H. Ellerbrock; Dominique Niessner; Detlef Deumlich; Daniel Puppe; Horst H. Gerke (Soil and Tillage Research, 2024)

Silicification patterns in wheat leaves related to ontogeny and soil silicon availability under field conditions - Jörg Schaller; Daniel Puppe; Jaqueline Busse; Silvia Paasch; Ofir Katz; Eike Brunner; Danuta Kaczoreck; Michael Sommer (Plant and Soil, 2022)